Advanced Attendance Management Systems: Technologies and Applications - Sakshi; Sharma, Chetan; Sharma, Shamneesh; Singh, Parminder; Khan, Ishtiyaq Ahmad (Edelweiss Applied Science and Technology, 2021)
The attendance management of the organization is an essential activity of their mundane life, has necessitated the need for revolutionary automatic attendance record-keeping and tracking systems. Paper surveys the emerging automated tools and applications which are popularly dominating this activity and fulfilling the requirement of accurate attendance marking systems. The technological era has gravitated more towards biometric attendance systems, but there are myriad other technologies that have been neglected thoroughly. The author identifies, extract, classify, and highlight all the evolving AMS (Attendance Management System) and have analyzed and compared their performances precisely and conscientiously. This survey identifies assorted AMS as biometric, NFC (Near Field Communication), RIFD (Radio Frequency Identification), Bluetooth, and cloud computing-based attendance systems. This article not only provides the literature review on the earlier work, but also provides an analytical report related to cloud-based AMS, discussions, and future recommendations.